Issues of state and public administration at the regional level in the context of the subject «Innovation Management» - Shorobura, Inna (Journal of Education, Health and Sport, 2024)
The issue of public administration at the regional level was considered in the context of the subject «Innovative Management». The development of local self-government is of great importance for Ukraine and its population. The territorial community is the main subject of local self-government, which has its own functions and powers. The main role in management is performed by local self-government bodies that interact with state administrations. Regional military administrations have become key in the system of coordination and management of military issues at the regional level. The public plays a significant role in military administration and ensuring national security through active participation in public administration.